Behavioural changes caused by lameness and lameness treatment in dairy cows housed in automatic milking systems in the UK - Miguel-Pacheco, Giuliana Giannina (2015)
Lameness is a detrimental problem for the welfare of cows and farmer profits; it causes changes in cow behaviour, which have direct impact on milk production as cows reduce their overall activity. The main aim of this thesis was to investigate behavioural changes caused by lameness and lameness treatment in cows housed in automatic milking systems; in addition it aimed to investigate the effect of claw horn lesions on the likelihood of recovery from lameness.